Capacity of Persons with Disabilities as Legal Subjects in Islamic Law - Ainul Yaqin; Khariri (Indonesian Academy of Social and Religious Research (IASRR), 2022)
The study of disability is one of the most important studies in Islam. In the study of Islamic law, the problem of disability is seen as one of the conditions that can cause the perpetrators to get various conveniences and tolerances in carrying out religious rules. However, this perspective is seen as still not enough to be a solution to the problem of disability. This is because this perspective still positions people with disabilities in a powerless position and still does not have the same opportunity to receive their legal rights as legal subjects. This study aims to examine in depth the position and capacity of persons with disabilities as legal subjects in Islamic law. The conclusion of this study is that persons with disabilities are legal subject with full rights as the normal people. They have the right and are capable of receiving and acting legally. In terms of receiving rights, persons with disabilities are full legal subjects. As in the field of ibadah, persons with disabilities have the capacity as full legal subjects but with tolerance according to their abilities. Meanwhile in the field of muamalah, persons with disabilities are subject to certain limitations in their capacity as legal subjects.